2019
DOI: 10.1111/mmi.14418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CodY RNome reveals RsaD as a stress‐responsive riboregulator of overflow metabolism in Staphylococcus aureus

Abstract: In Staphylococcus aureus, the transcription factor CodY modulates the expression of hundreds of genes, including most virulence factors, in response to the availability of key nutrients like GTP and branched‐chain amino acids. Despite numerous studies examining how CodY controls gene expression directly or indirectly, virtually nothing is known about the extent to which CodY exerts its effect through small regulatory RNAs (sRNAs). Herein, we report the first set of sRNAs under the control of CodY. We reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 102 publications
(155 reference statements)
1
27
0
Order By: Relevance
“…Then, in these conditions, RsaD must be repressed for survival. This work revealed the trans-acting regulatory activity of RsaD on at least one mRNA and highlights the balancing role of this sRNA in carbon overflow and its implications in cell survival (Augagneur et al, 2020). All these mechanisms by which RsaD might be regulated, integrate, and respond to different environmental cues remain to be unveiled.…”
Section: The Blurred Line Between Metabolism and Virulence: Rsad Rsae Rsai And Rsagmentioning
confidence: 88%
See 3 more Smart Citations
“…Then, in these conditions, RsaD must be repressed for survival. This work revealed the trans-acting regulatory activity of RsaD on at least one mRNA and highlights the balancing role of this sRNA in carbon overflow and its implications in cell survival (Augagneur et al, 2020). All these mechanisms by which RsaD might be regulated, integrate, and respond to different environmental cues remain to be unveiled.…”
Section: The Blurred Line Between Metabolism and Virulence: Rsad Rsae Rsai And Rsagmentioning
confidence: 88%
“…Nonetheless, the exact mechanism of rsaD regulation by this factor remains uncertain. More recently, Augagneur et al (2020) observed that expression of rsaD is repressed by CodY, a global regulator activated by branched amino-acids and GTP and regulating genes involved in primary metabolism and virulence ( Brinsmade, 2017 ). The promoter region of rsaD contains a putative CodY binding motif, which was detected in at least 15 staphylococcal species, indicating that the regulation of rsaD by CodY is probably conserved ( Augagneur et al, 2020 ).…”
Section: The Blurred Line Between Metabolism and Virulence: Rsad Rsae Rsai And Rsagmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be part of the RsaI regulon, and is induced upon nitric oxide challenge ( Bronesky et al, 2019 ). A study of the CodY regulon identified RsaD as a direct molecular target, and computational tools enabled the authors to find various RsaD mRNA targets including alsS , which encodes α-acetolactate synthase ( Augagneur et al, 2020 ). Through post-transcriptional repression of alsS , RsaD redirects carbon overflow metabolism and regulates cell death during exposure to a weak acid stress.…”
Section: Srna Regulation Is Required For a Variety Of Biological Functionsmentioning
confidence: 99%